Avaliação do tratamento hidrotérmico, combinado ao cálcio e ao ácido giberélico, na resposta do tomate ao chilling - Zachow, Karine (2011)
Tomato (Lycopersicon esculentum Mill) is subject to chilling injury during cold storage. The application of calcium and plant growth regulators in post-harvest may help to reduce a number of physiological disorders on fruits. In this work were verified the influence of the application in post-harvest of the five treatments: control, without heat shock; only heat shock; heat shock + Ca 2 %; heat shock + GA3 100 mg L-1; and heat shock + Ca 2 % + GA3 100 mg L-1, associated with hydrothermal treatment (45 °C) for 12 min of immersion in the response of tomato to the "chilling" and check the physical and chemical composition, the bioactive compounds and enzyme activity of the fruit. The fruits were stored at 5 °C and relative humidity of 80 % for a period of ten days. The evaluations were made ten days after removal of the fruits of the cooling conditions. The design was completely randomized with five treatments and five repetitions, each repetition being characterized by a fruit. Was applied to the ANOVA results, and when the parameter was significant, the averages were compared by Tukey test, at 5 % probability. The use of heat shock treatment was effective in reducing pathogens in tomato fruits after cold storage. Treatment with heat shock + Ca 2 % + GA3 100 mg L-1 was the best among the rest, because it provided a higher concentration of ascorbic acid, as well as β-carotene and total phenols in the fruits treated and caused a reduction in the incidence of pathogens. The use of GA3 showed better results compared to Ca, when combined with heat shock, the fruits response to the effects of cold storage, requiring further investigation in this direction